KEGIATAN PABRIKASI MESIN PENGUPAS BAWANG MERAH MEREK BEJE TIPE PB 01 - Annisa Nur Ichniarsyah; Titis Pury Purboningtyas; Widiya Apriliani (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2021)
Shallot peeling activities in small scale industry are still manually done. This process takes huge time and effort. Therefore, shallot dehuller was designed and developed to increase effectivity and efficiency. The objectives of the study were to develop shallot dehuller machine and conduct functional tests. Identification tests indicated workshop tools needed for machine development were grinder, rulers, scales, and various machines such as drilling, welding, roll and bender, and cutting plasma machine. Machine development started from manufacturing the frames, dehuller hopper and inlet, rotating disc, outlet for shallot hull, and outlet for shallot. Functional tests indicated that the machine construction was according to the design plan.